Split topicalization as remnant movement: the case of Jordanian Arabic - Eman Al Khalaf (Cogent Arts & Humanities, 2024)
This paper empirically and theoretically investigates the syntax of split topicalization in Jordanian Arabic, a previously undiscovered phenomenon. The results of a large-scale acceptability judgment task (n = 463) reveal that Jordanian Arabic displays split topicalization of various categorial types. Building on the labeling framework, the remnant movement analysis and the idea that there exists an IP-internal focus position below T and above the vP phase, I propose a unified analysis of all the categorial types of ST in Jordanian Arabic, where ST is reduced to remnant movement of a constituent (NP, VP, AP, etc.), from which a subconstituent has undergone focus movement to an IP-internal focus position. The analysis captures all cases of ST in Jordanian Arabic, such as splitting with ditransitives. It accounts for the fact that ST in JA is only grammatical with bridge-contour intonation: the intonation is read off the syntactic structure in which functional projections such as TopP and FocP are encoded. The analysis provides insights into the structure of the left periphery of the vP phase: it lends support to the view that this area could have a more elaborate structure than previously thought, parallel to that of the left periphery of the CP phase.